Advance of Electroconductive Hydrogels for Biomedical Applications in Orthopedics - Jian Cao; Zhongxing Liu; Limin Zhang; Jinlong Li; Haiming Wang; Xiuhui Li (Advances in Materials Science and Engineering)
Electroconductive hydrogels (EHs) are promising composite biomaterials of hydrogels and conductive electroactive polymers, incorporating bionic physicochemical properties of hydrogels and conductivity, electrochemistry, and electrical stimulation (ES) responsiveness of conductive electroactive polymers. The biomedical domain has increasingly seen EHs’ application to imitating the biological and electrical properties of human tissues, acclaimed as one of the most effective biomaterials. Bone’s complex bioelectrochemical properties and the corresponding stem cell differentiation affected by electrical signal elevate EHs’ application value in repairing and treating bone, cartilage, and skeletal muscle. Noteworthily, the latest orthopedic biological applications require broader information of EHs. Except for presenting the classification and synthesis of EHs, this review recapitulates the advance of EHs application to orthopedics in the past five years and discusses the pertinent development tendency and challenge, aiming to provide a reference for EHs application direction and prospect in orthopedic therapy.